SIKAP SULTAN SYARIF KASIM II ABDUL JALIL SYAIFUDIN TERHADAP KEMERDEKAAN INDONESIA - Ricko Rahmad; Ridwan Melay; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The word Siak Sri Inderapura, literally can mean the city center of a religiously devout king, in Sanskrit, sri means